PENGARUH TERAPI MUROTAL AL QURAN TERHADAP PENURUNAN NYERI BERSALIN KALA 1 FASE AKTIF DI PMB VARIA MEGASARI - Sari, Ayu Puspita; Winarni, Winarni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Childbirth is a process of expelling the products of conception that have reached term or can survive outside the womb through the birth canal or other means with or without assistance. One of the problems during the birthing process is labor pain. Pain is an uncomfortable feeling caused by certain stimuli. Effort to overcome labor pain with murotal Al Qur’an therapy. Listening to Al Qur’an murotals can redude stress hormones, activate endorphin hormones naturally, provide a sense of calm and create a relaxed atmosphere. Objective: To determine the effect of Al Qur’an murotal therapy on reducing labor pain during the first active phase. Method: The research design uses a pre experimental design with a one grup pre test post test design. Sampling was taken using consective sampling with a total sample of 23 mothers giving birth. Results: The results of data analysis showed that the majority of respondents before being given Al Qur’an murotal therapy were in severe pain, 17 respondents (73.9%). After being given murotal Al Qur’an therapy, the majority had moderate pain, namely 16 respondents (68.9%). The results of the Wilcoxon test showed that there was an effect of Al Qur’an murotal therapy on reducing labor pain during the first active phase at the Independent Practice of Midwives Varia Megasari with a p value of 0.000 (p value < 0.05). Conclusion: Murotal Al Qur’an has an effect on reducing labor pain during the 1st active phase in the Independent Practice of Midwives Varia Megasari. Health workers can use murotal Al Qur’an as an anternative to overcome the problem of reducing pain in birthing mothers.